Advantages of chinese production in the context of globalization - W. Yuanlong; W. Xizhe (Informaciâ i Innovacii)
A large number of exports of cheap industrial products completed the initial accumulation of capital in China, but this manufacturing industry, which has not mastered the basic technologies, is very fragile. With the development of science and technology, the economy of various countries is gradually globalizing. China is currently the second largest economy in the world, and due to its large population, this also makes China a huge sales market, but due to the large amount of excess capacity, China’s excess industrial market cannot be digested by its own country. In addition to the modernization of China’s manufacturing industry, it is inevitable that Chinese industry will simultaneously enter the world market. China’s manufacturing industry will face diﬃculties, but at the same time it has its own unique advantages.